ROLE AND IMPORTANCE OF ACCOUNTING AND AUDIT IN CORPORATE GOVERNANCE - Lovre, Ivan K (International Journal of Economic Practice and Policy, 2014)
The current economic crisis and the financial scandals of the early XXI century led to the discrediting and compromising the accounting and auditing profession. The assumption of efficient growth and development of a company is an introduction of corporate governance and protection of the interests of creditors. In order to regain public confidence in financial reporting, it is necessary to examine the role of accounting and auditing profession and align it with international standards. It is necessary to take into account The OECD Principles of Corporate Governance, which are accepted by all international financial and accounting organizations, with the aim of rehabilitation of confidence in the audit. Taking into account The OECD Principles, it becomes necessary for accounting and auditing practices to be directed towards the fulfillment of the basic role of protecting the interests of stakeholders and providing information for the functioning of the administration.